Interdisciplinary Sequences: A Conceptual Commentary - Mani Man Singh Rajbhandari (Journal of Interdisciplinary Sciences)
This paper presents a conceptual commentary on interdisciplinary sequencing, an idea proposed to interlink and interconnect the academic variables from multidisciplinary studies. Interdisciplinary sequencing connects academic variables through reasonable consensus on common grounds. Literature published in the Journal of Interdisciplinary Sciences aims to stimulate a better understanding of interdisciplinary sequencing by creating reasonable common ground. The journal also aims to illustrate the outcomes of academic publications towards mindfulness, through shared knowledge on wellbeing and wellness towards the betterment of socio-psycho-polity, to achieve a healthy environment from within and between multidisciplinary areas. Although it may appear unrealistic, multidisciplinary discourse in academia is possible and interesting. However, the margin of error, and the manner of mistakes, needs to be taken into consideration, which is possible by applying appropriate Skills, Ability, Knowledge, Competence and Intelligence (SAKCI)